2014
DOI: 10.1111/resp.12345
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Ki‐67, p53, transforming growth factor‐β and lysyl oxidase in the metastasis of lung cancer

Abstract: LOX and TGF-β may play roles in metastatic AC. LOX and TGF-β may become markers of metastatic disease and inhibition could be explored for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…TGF-␤ superfamily proteins have been demonstrated to play important roles in cell proliferation, migration and invasion (Drabsch and ten Dijke, 2012; Sun et al, 1995), and their aberrant expression and activity is associated with a variety of tumors (Araz et al, 2014;Chou et al, 2010;Giannelli et al, 2014;Zhang et al, 2014). Here we showed that overexpression of LRG1 activated TGF-␤ signaling in glioma cells by upregulating TGF-␤1 and promoting the phosphorylation of its downstream Smad proteins ( Fig.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…TGF-␤ superfamily proteins have been demonstrated to play important roles in cell proliferation, migration and invasion (Drabsch and ten Dijke, 2012; Sun et al, 1995), and their aberrant expression and activity is associated with a variety of tumors (Araz et al, 2014;Chou et al, 2010;Giannelli et al, 2014;Zhang et al, 2014). Here we showed that overexpression of LRG1 activated TGF-␤ signaling in glioma cells by upregulating TGF-␤1 and promoting the phosphorylation of its downstream Smad proteins ( Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Binding of TGF-␤ with its type I and type II receptors leads to phosphorylation and activation of smad2 and smad3, which in turn bind to smad4 and modulate cell functions (Kamato et al, 2013). The aberrant expression and activity of TGF-␤ has been shown to be associated with a variety of tumors including lung (Araz et al, 2014), liver (Giannelli et al, 2014), breast and ovarian cancer (Chou et al, 2010). LRG1 was recently demonstrated to promote endothelial cell proliferation and angiogenesis via TGF-␤ signaling pathway (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…The TGF-β superfamily of proteins, ubiquitous in cells, are widely involved in cell development and progression, and their excessive expression is found in a variety of tumors including lung, liver, breast, and ovarian cancers [32][33][34][35]. The Smad cytoplasmic proteins, a series of key proteins in the TGF-β signaling pathway, are present in both normal and transformed cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Relatively slow‐growing Ad lesions frequently metastasize. Araz et al . examined the correlations between the Ki‐67, p53, transforming growth factor (TGF)‐b and lysyl oxidase (LOX) values and the metastatic stage in various types of lung cancers.…”
Section: Lung Cancermentioning
confidence: 99%
“…Relatively slowgrowing Ad lesions frequently metastasize. Araz et al 12 examined the correlations between the Ki-67, p53, transforming growth factor (TGF)-b and lysyl oxidase (LOX) values and the metastatic stage in various types of lung cancers. Consequently, high levels of cellular LOX and TGF-b were found to be related to an increased incidence of distant metastasis in Ad patients.…”
Section: Diagnosismentioning
confidence: 99%